Does the threat of suspension curb dangerous behavior in soccer? A case study from the premier league - VanDerwerken, D. N.; Rothert, J.; Nguelifack, B. N. (Journal of Sports Economics, 2018)
Using data from the 2011-2012 season of the Premier League, we study empirically and theoretically the impact of soccer suspension rules on the behavior of players and referees. For players facing a potential one-game suspension, being one versus two yellow cards away from the suspension limit results in an approximate 12% reduction in fouling, while for those facing a potential two-game suspension, the reduction is approximately 23%. The probability such players receive a yellow card is also reduced. In addition, we find some evidence of slight referee bias for the home team in the dispensing of penalty cards, but not in the calling of fouls. Finally, we develop a theoretical framework for investigating the effects of suspension rules on the number of fouls committed. Within this framework, we investigate how policy instruments such as referees` propensity to give out yellow cards or their consistency in giving them out affect the impact of suspension rules.